Interaction of magnesium ions in high temperature aqueous solution with Incoloy-800. (December 2022) - C, Sinu; S, Veena; H, Subramanian; S, Bera; P.K., Aji Kumar; P, Chandramohan; Mathews, Tom; TV, Krishna Mohan
Abstract: Corrosion and activated corrosion product deposition in the out of core surfaces is a major concern in Pressurized Heavy Water Reactors (PHWRs) as it causes radiation exposure to plant personnel during routine maintenance. The ability of added Mg 2+ ions in the coolant to mitigate these undesirable effects in Carbon Steel structural material is known. By contrast, its effect on other heat transfer surfaces in the Primary Heat Transport (PHT) system is largely unknown. This paper presents a detailed study on the role of Mg 2+ ions in modifying the oxide on Incoloy-800. Incoloy-800 was exposed to normal and Mg 2+ ion modified alkaline water chemistry in a once through loop. Mg 2+ incorporation into the ferrite lattice was indicated in Raman, GIXRD analysis and corroborated by XPS technique. The incorporation of Mg 2+ ions in the oxide films resulted in a higher total impedance and reduced passive current density when compared to the films without Mg 2+ ions. Thus oxide with Mg 2+ ions improves the general corrosion resistance and does not induce localised corrosion in the material. Graphical Abstract: ga1 Highlights: Passive films formed on Incoloy under simulated PHT conditions, incorporated Mg 2+ ions from solution into the ferrite lattice. Mg Modified films were more compact and less porous. Higher impedance and lower point defects were observed for Mg containing films. Mg incorporation resulted in reduction of metal release at metal/oxide interface.